Land tenure, land use antecedents, and willingness to embrace resilient farming practices among smallholders in Nigeria - Kehinde, Mojisola Olanike; Shittu, Adebayo Musediku; Oriade, Opeyemi Abosede; Edewor, Sarah Edore (Frontiers in Sustainable Food Systems, 2023)
Introduction Shifting to Resilient Farming Practices (RFPs) is crucial in building resilience to climate change and reducing greenhouse gas emissions. This study seeks to assess how land tenure and land-use antecedents affect the willingness of smallholder farmers (SHFs) to embrace RFPs in Nigeria. Methods The respondents were selected in a multi-stage random sampling process across 16 States and 192 farming communities, yielding a final sample of 1,344 SHFs that cultivate maize and/or rice. The RFPs include a set of good agricultural practices (GAPs), GAPs with manure application and GAPs with agroforestry as against the status quo of conventional agricultural practices. Data were analyzed using descriptive and regression methods. Results and discussion The results show that 20% of the respondents were willing to adopt agroforestry while 25% and 37% were willing to adopt GAPs with and without manure application respectively. On the other hand, about 18% preferred to stick to the status quo. The multinomial logit result shows that RFPs were significantly influenced by age, education and gender of the household head, membership of the cooperative, household size, land acquisition through inheritance and purchase, newly deforested land, mechanical clearing, and bush burning. The study suggests that land titling and some level of perceived tenure security are necessary conditions for smallholder farmers to embrace RFPs in Nigeria.